2022
DOI: 10.1021/acsami.1c22138
|View full text |Cite
|
Sign up to set email alerts
|

Local Elimination of Senescent Cells Promotes Bone Defect Repair during Aging

Abstract: Due to the declined function of bone marrow mesenchymal stem cells (BMSCs), the repair of bone defects in the elderly is retarded. Elimination of senescent cells emerges as a promising strategy for treating age-related diseases. However, whether the local elimination of senescent BMSCs can promote bone regeneration in the elderly remains elusive. To tackle the above issue, we first screened out the specific senolytics for BMSCs and confirmed their effect of eliminating senescent BMSCs in vitro. Treatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…It may also be likely that bioengineered delivery vehicles will need to be combined with the senolytic agents to optimize the dosage and efficacy of this strategy. Recently, Xing et al reported quercetin delivered by hydrogel as an effective senolytic that locally eliminated senescent BM-MSCs in vitro and restored the self-renewal capacity as well as the osteogenic ability as a result [ 205 ].…”
Section: Therapeutic Approaches To Rejuvenate Aged Mscsmentioning
confidence: 99%
“…It may also be likely that bioengineered delivery vehicles will need to be combined with the senolytic agents to optimize the dosage and efficacy of this strategy. Recently, Xing et al reported quercetin delivered by hydrogel as an effective senolytic that locally eliminated senescent BM-MSCs in vitro and restored the self-renewal capacity as well as the osteogenic ability as a result [ 205 ].…”
Section: Therapeutic Approaches To Rejuvenate Aged Mscsmentioning
confidence: 99%
“…When a hydrogel is employed as the carrier for the local administration of Que, the key issue concerned is how to efficiently load enough amount of Que into the hydrogel and manage its controlled and sustained release. Direct loading of Que into hydrogels with the aid of organic solvents such as ethanol and dimethyl sulfoxide has been explored [ 33 , 36 , 53 ]. In doing so, the organic solvent should be removed from the resulting hydrogels otherwise such Que-loaded hydrogels may cause potential side effects due to the solvent release; in addition, this kind of Que-loaded hydrogel usually shows a severe initial burst because in many cases, hydrogels constructed with natural polymers have limited ability to administer the controlled and sustained release of drugs or biomolecules [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the present instance, Que was first loaded into ABG NPs and the resulting NPs were then embedded into CH-CY gels. In comparison to some Que-loaded hydrogels reported in the literature [ 33 , 36 , 53 , 54 , 55 ], presently developed Que-loaded composite hydrogels can fulfill several missions at the same time: (I) the Que-load in the composite gels can be tailored by altering either the Que-load in ABG NPs or the content of Que-loaded ABG NPs in the composite gels; (II) ABG NPs would contribute significantly to the mechanical enhancement of the composite gels; and (III) ABG NPs would cooperate with the gel matrix to synergistically modulate the release of Que. Figure 5 C presents the Que release profiles for GEL-1, GEL-2, and GEL-3 gels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The removal of senescent cells represents a paradigm shift in medicine 45 . Targeted selective killing of senescent cells using platforms based on nanomaterials has the potential to fight various age-related diseases [46][47][48][49][50] . A fundamental issue to advance on the application of nanomedicine tools onto aging is to understand how NPs uptake and accumulate under senescence conditions.…”
Section: Discussionmentioning
confidence: 99%